KAJI TERAP PERBEDAAN SUHU INKUBASI TELUR TERHADAP DERAJAT PEMBUAHAN, DERAJAT PENETASAN TELUR DAN SINTASAN LARVA IKAN NILA NIRWANA Oreochromis niloticus - Wahyudi, Imam Tri; Hernawan, Systa Ambar Wangi; Hendriana, Andri; Abdurahim, Abdurahim; Ramadhani, Dian Eka; Iskandar, Andri (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2025)
One of the problems in tilapia fish farming is the low hatching rate of eggs. To improve the success of egg hatching, temperature management is necessary. This research aims to determine the effect of different temperatures on the production performance of tilapia fish. The research used four different treatments, namely the Control treatment (temperature 25°C), treatment P1 (temperature 28°C), treatment P2 (temperature 30°C), and treatment P3 (temperature 32°C). The observed parameters include fertilization rate, hatching rate, survival rate, and water quality. The research findings indicate that the highest FR is found in treatment P3, with a value of 96%, and tends to decrease in the treatment control with a value of 81.67%. The highest HR is found in treatment P2 with a value of 96.67% and tends to decrease in treatment control with a value of 67.33%. The highest SR is found in treatment P3 with a value of 86.33% and tends to decrease in treatment control with a value of 52.33%. The optimal production performance of nirwana tilapia fish is achieved at a temperature of 30°C.